Association between Placenta Accreta and History of Previous C-Section and position of Placenta in Pregnant Women presenting at A Public Sector Hospital of Punjab, Pakistan: a cross-sectional analysis - Safia Ashraf, Memoona Hanif, Muhammhad Abdul Aziz, Saba Akram, Fouzia Khadim, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Placenta accreta is a rare and life threatening disease during pregnancy and causes must be sorted out for its early diagnosis and treatment. Aim: To find the association between placenta accreta and history of previous C-section in pregnant women. Methods: This analytical cross-sectional survey was conducted at Radiology department of DHQ teaching hospital Gujranwala from 1st January, 2022 to 31st March, 2022. A self-administered questionnaire was filled by the pregnant women at the gynecology and obstetrics outdoor department. Data was analyzed by using SPSS-Version 26. Results: AFI and age were found to be normally distributed while all other variables were non-normally distributed. Mean ± S.D of AFI was 10.75 ± 3.99 while mean ± S.D for age were 27.05 ± 3.90. Median ± IQR for gestational age of the study participants was 33.1 ± 8.98. While median ± IQR for body weight and heart rate of the study participants were 2052 ± 1632 and 147 ± 11 respectively. The association of the placenta accreta with history of C-Section was found to be highly statistically significant in our study (P=0.012). Conclusion: It was evident from our study that plecenta accreta was associated with history of C-Section hence the multiparous with history of C-Section should undergo repeated scans for early diagnosis of placenta previa and the patients also need to have a proper follow-up as per consultant’s advice.